2013
DOI: 10.1371/journal.pone.0069817
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of Proanthocyanidins or Docosahexaenoic Acid Reversess the Increase of miR-33a and miR-122 in Dyslipidemic Obese Rats

Abstract: miR-33 and miR-122 are major regulators of lipid metabolism in the liver, and their deregulation has been linked to the development of metabolic diseases such as obesity and metabolic syndrome. However, the biological importance of these miRNAs has been defined using genetic models. The aim of this study was to evaluate whether the levels of miR-122 and miR-33a in rat liver correlate with lipemia in nutritional models. For this purpose, we analyzed the levels of miRNA-33a and miR-122 in the livers of dyslipide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 53 publications
4
51
0
1
Order By: Relevance
“…Moreover, several studies based on the effect of polyphenols and polyphenol-rich extracts on miRNAs expression indicated that each polyphenol targets specific miRNAs in liver (19,22,23). Hence, this suggests that the type of polyphenol influence the miRNA’s modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies based on the effect of polyphenols and polyphenol-rich extracts on miRNAs expression indicated that each polyphenol targets specific miRNAs in liver (19,22,23). Hence, this suggests that the type of polyphenol influence the miRNA’s modulation.…”
Section: Discussionmentioning
confidence: 99%
“…There is additional evidence that dietary composition may influence the TG‐lowering ability of GSPE, which is suggested by studies using a high‐fat, high‐sugar “cafeteria diet” as a way to induce dyslipidemia . While some studies showed reduced serum TG levels with GSPE treatment in such a model, many have not .…”
Section: Grape Seed Procyanidin Extractmentioning
confidence: 99%
“…There is additional evidence that dietary composition may influence the TG‐lowering ability of GSPE, which is suggested by studies using a high‐fat, high‐sugar “cafeteria diet” as a way to induce dyslipidemia . While some studies showed reduced serum TG levels with GSPE treatment in such a model, many have not . The cafeteria diet used in such studies allows the animals the option to freely consume not only high‐fat, high‐sugar foods, such as bacon, cheese, biscuits with paté, muffins, and sweetened milk but also standard chow and even low‐fat, high‐fiber foods such as raw carrots .…”
Section: Grape Seed Procyanidin Extractmentioning
confidence: 99%
“…Una menor expresión del gen PLIN4 debida al miR-522 podría contribuir a fenotipos relacionados con la obesidad, pero son necesarios más estudios para corroborarlo, así como para encontrar si el mecanismo propuesto puede darse para otros miARN. En otro trabajo reciente, Baselga et al 82 efectos dislipidémicos de 2 miARN al suplementar la dieta de ratas obesas con proantocianidinas y DHA. Los miARN analizados (miR-122 y miR-33a) son importantes reguladores del metabolismo lipídico en el hígado 83 .…”
Section: Resultados Y Discusiónunclassified